Is referral of postsurgical colorectal cancer survivors to cardiac rehabilitation feasible and acceptable? A pragmatic pilot randomised controlled trial with embedded qualitative study. Issue 1 (4th January 2016) - Hubbard, Gill; Adams, Richard; Campbell, Anna; Kidd, Lisa; Leslie, Stephen J; Munro, Julie; Watson, Angus
Abstract : Objectives: (1) Assess whether cardiac rehabilitation (CR) is a feasible and acceptable model of rehabilitation for postsurgical colorectal cancer (CRC) survivors, (2) evaluate trial procedures. This article reports the results of the first objective. Design and setting: A pragmatic pilot randomised controlled trial with embedded qualitative study was conducted in 3 UK hospitals with CR facilities. Descriptive statistics were used to summarise trial parameters indicative of intervention feasibility and acceptability. Interviews and focus groups were conducted and data analysed thematically. Participants: People with CRC were considered for inclusion in the trial if they were ≥18 years old, diagnosed with primary CRC and in the recovery period postsurgery (they could still be receiving adjuvant therapy). 31% (n=41) of all eligible CRC survivors consented to participate in the trial. 22 of these CRC survivors, and 8 people with cardiovascular disease (CVD), 5 CRC nurses and 6 CR clinicians participated in the qualitative study. Intervention: Referral of postsurgical CRC survivors to weekly CR exercise classes and information sessions. Classes included CRC survivors and people with CVD. CR nurses and physiotherapists were given training about cancer and exercise. Results: Barriers to CR were protracted recoveries from surgery, ongoing treatments and poor mobility. No adverse events were reported during the trial, suggesting that CR is safe. 62% of participants completed the intervention as per protocol and had high levels of attendance. 20 health professionals attended the cancer and exercise training course, rating it as excellent. Participants perceived that CR increased CRC survivors' confidence and motivation to exercise, and offered peer support. CR professionals were concerned about CR capacity to accommodate cancer survivors and their ability to provide psychosocial support to this group of patients. Conclusions: CR is feasible and acceptable for postsurgical CRC survivors. A large-scale effectiveness trial of the intervention should be conducted. Trial registration number: ISRCTN63510637.